Movement of sturgeons (Acipenser oxyrinchus oxyrinchus and A. fulvescens) in the St. Lawrence Estuary: A 35‐year tagging study. (16th June 2021) - Paradis, Yves; Pépino, Marc; Bernatchez, Simon; Fournier, Denis; L'Italien, Léon; Doucet‐Caron, Jérôme
Abstract: Movement of Atlantic sturgeon ( Acipenser oxyrinchus oxyrinchus) and lake sturgeon ( A. fulvescens) in the St. Lawrence Estuary (Québec, Canada) are not fully understood. To assess the movement extent of both species, a mark–recapture study was conducted in collaboration with commercial fishermen operating in the St. Lawrence Estuary. Between 1981 and 2015, 3, 367 Atlantic sturgeon (fork length 21.8–199.5 cm) and 3, 180 lake sturgeon (fork length 17.8–190.8 cm) were tagged and released. Of these, 673 Atlantic sturgeon and 42 lake sturgeon were recaptured. The maximum distances traveled between capture and recapture locations were 1, 307 km for Atlantic sturgeon (8 years after initial capture) and 252 km for lake sturgeon (less than 1 year after initial capture). Statistical analyses identified differences in the dispersal distance of both species as revealed by a first component characterized by individuals with short dispersal distances (98% and <35 km for Atlantic sturgeon; 58% and <1 km for lake sturgeon) and a second component characterized by individuals with longer dispersal distances (2% and >600 km for Atlantic sturgeon; 42% and >190 km for lake sturgeon). We suggest that the short dispersal distances detected in the vast majority of Atlantic sturgeon recaptures likely reflect strong site fidelity, highlighting the importance of the St. Lawrence Estuary as a preferred habitat for juveniles and subadults. Although recaptures were low for lake sturgeon because this species is only marginally targeted by commercial fishermen in the St. Lawrence Estuary, our results also showed that this species uses estuarine habitats and that half of the population seems to exhibit strong site fidelity (67% of individuals were recaptured within 2 km).